Resilience and Personal Development in the Workplace: The Effect of Intervention Programs on Employee Wellbeing - Sakura Suzuki; Ren Suzuki; Josefa Flores (Research Psychologie, Orientation et Conseil, 2025)
Workplace resilience and personal development are critical factors influencing employee well-being and organizational success. Modern workplaces present numerous challenges, including high stress levels and rapid changes, necessitating effective strategies to enhance resilience and promote personal growth. Intervention programs have emerged as a promising approach to address these challenges, yet their impact on employee well-being requires further empirical investigation. This study examines the effect of workplace intervention programs on employee resilience, personal development, and overall well-being. A mixed-methods design was employed, incorporating both quantitative and qualitative approaches. The study involved 150 employees from diverse industries, divided into intervention and control groups. The intervention group participated in a 10-week program that included resilience training, mindfulness practices, and goal-setting workshops. Data were collected through standardized well-being assessments, resilience scales, and semi-structured interviews. The findings revealed significant improvements in resilience scores and well-being indicators among the intervention group compared to the control group (p < 0.01). Participants reported enhanced emotional regulation, stress management, and self-efficacy. Qualitative insights highlighted increased motivation and a stronger sense of purpose as key outcomes of the program.